The Influence of African Traditional Religion on Biodiversity Conservation in Anambra East LGA of Anambra State, Southeastern, Nigeria: A Geospatial Information System Study - Okafor, Uchenna Paulinus (Journal of Asian and African studies, 2025)
This study applies geospatial information techniques in the study of the influence of African traditional religion on biodiversity conservation in Anambra East Local Government Area of Anambra State, Nigeria. Satellite images of the sacred forests captured along with their surrounding environment constitute spatial data sets which were analyzed for land use/land cover changes (LULCC). Results showed that vegetal covers around Udude Onogu and Olio-olio forest shrines decreased by 10.66% and 30.73%, respectively, while built-up areas of the same environment grew by 15.93% and 7.45% between 1980 and 2020. Findings show that the African traditional religious belief system influences biodiversity conservation.